Developing an Interactive Digital Handout for Momentum and Impulse Material Physics in High Schools - Pahlawan, Ridho; ., Ismet; ., Syarifuddin (Journal of Education Technology, 2021)
Developing an Interactive Digital Handout for Momentum and Impulse Material Physics in High Schools. Objective: to develop an interactive digital handout of momentum and impulse physics material in high schools. Methods: this study was conducted by giving students a pretest-posttest on momentum and impulse material. Findings: The average learning outcomes before being given the interactive digital handout display of the material physics material momentum and impulse is 48.93. Then the educator gave teaching using an interactive digital physics handout device using the articulate storyline application to increase the average score of cognitive learning outcomes of students to 81.27. The increase in the mean value of students was measured using the N-gain Score and the results were 0.70 in the medium category. Conclusion: e-learning tools have been tested effective to improve student learning outcomes seen from the N-gain of 0.70 which is included in the moderate category.